Analisis Strategi Pemasaran dalam Meningkatkan Jumlah Kunjungan Wisatawan dalam Perspektif Bisnis Syariah : (Studi Kasus : Taman Margasatwa dan Budaya Kinantan Bukittinggi, Sumatera Barat) - Erni Oktafia; Rahmi Rahmi (Universitas 17 Agustus 1945 Semarang, 2024)
Every company must have a certain strategy to attract the attention of consumers (visitors). Seeing the decline in the number of visitors to the Kinantan Wildlife and Cultural Park in 2023. TMSBK has carried out renovations aimed at beautifying it and attracting the attention of visitors. Regarding this renovation, it is included in one of the marketing mix (7P), namely Physical Evidence. According to Kotler and Armstrong, Physical Evidence is one of the real things that influences consumers' decisions to buy and use the products or services offered. However, what happened was that the number of visitors decreased. The research method used is to use a field research method or qualitative field research, namely direct observation of the object being studied in order to obtain relevant data. The primary data source in this research is the management of TMSBK Bukittinggi, while the secondary data source is the visitors of TMSBK Bukittinggi. According to the research findings, the IFAS matrix score of 2.57 suggests that the company holds a strong internal position. Conversely, the EFAS matrix score of 2.40 indicates a weak external position for the company. This means that the company does not take advantage of existing opportunities or avoid external threats. Then, seen from a sharia business perspective, TMSBK has not been optimal in implementing the sharia business concept, because in Islam itself good business will provide mutual benefits between the company and visitors, especially in providing services to visitors. However, TMSBK focuses more on renovating tourist attractions and does not prioritize services to provide comfort to visitors.